2014
DOI: 10.1001/jamaoto.2014.2830
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Robot-Assisted Neck Dissection in Head and Neck Cancer

Abstract: We explored the RAND learning curve in a single institution over a 3-year period. This study can be used as a timeline reference for institutions where the RAND procedure will be adopted as an alternative procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
1
18
0
2
Order By: Relevance
“…Koh's group in South Korea has shown a 53% decrease in operative time in robot-assisted supraomohyoid neck dissection. 20 In this report, we demonstrate the feasibility of performing RAND on patients with known locoregional disease as well as a history of previous radiation therapy to the nodal basins. We operated on 5 patients with known neck disease, including 2 who had been previously irradiated.…”
Section: Discussionmentioning
confidence: 78%
“…Koh's group in South Korea has shown a 53% decrease in operative time in robot-assisted supraomohyoid neck dissection. 20 In this report, we demonstrate the feasibility of performing RAND on patients with known locoregional disease as well as a history of previous radiation therapy to the nodal basins. We operated on 5 patients with known neck disease, including 2 who had been previously irradiated.…”
Section: Discussionmentioning
confidence: 78%
“…Numerous publications have shown the safety and favorable outcomes of retroauricular robotic neck dissections, without any major complications or surgery related deaths (Albergotti et al, 2016; Albergotti, Kenneth Byrd, De Almeida, Kim, & Duvvuri, 2014; Byeon et al, 2014; Byeon et al, 2015; Kim et al, 2014; Kim et al, 2015; Kim, Chang, et al, 2013; Kim, Koh, et al, 2013; Lee et al, 2012; Lira, Chulam, de Carvalho, et al, 2018; Lira, Chulam, & Kowalski, 2018; Morton, Gray, Tandon, Izzard, & McIvor, 2009; Park et al, 2013; Shin, Choi, Kim, & Koh, 2014; Tae et al, 2013; Tae et al, 2014). A systematic review and meta‐analysis including 11 studies and more than 200 patients confirmed the significantly longer operative time in the group of patients who underwent robotic neck dissection.…”
Section: Reported Resultsmentioning
confidence: 99%
“…In a prospective study, Kim et al (2014) evaluated the learning curve for neck dissection by retroauricular approach. There were 50 modified radical neck dissections and 40 selective neck dissections performed by a single surgeon using the robotic system.…”
Section: Learning Curvementioning
confidence: 99%
“…However, the duration of surgery in RAND interventions is significantly reduced after respective training. In a publication by Kim et al, 90 head and neck cancer patients underwent RAND performed by only one surgeon 77 . In the group of modified radical neck dissection as well as in the group of supraomohyoidal neck dissection, the duration of surgery could be significantly reduced in the course of the study (298 ->212; 226 ->106 min, respectively).…”
Section: Cervical Soft Partsmentioning
confidence: 99%
“…Allerdings wird die Operationszeit bei RAND-Eingriffen durch entsprechendes Training deutlich reduziert. In der Publikation von Kim et al wurden 90 Kopf-Hals-Karzinom-Patienten durch einen einzigen Operateur mittels RAND operiert 77 . Sowohl in der Gruppe der modifiziert radikalen Neck dissection als auch bei der supraomohyoidalen Neck dissection konnte die Operationszeit im Verlauf der Studie signifikant reduziert werden (298 -> 212; 226 -> 106 Min).…”
Section: Halsweichteileunclassified